Performance of Islamic Equity Fund in Indonesia and Malaysia - Ainun Zamilah (Departement of Mathematics Education, 2023)
This study aims to measure the performance of Indonesian and Malaysian Islamic stock mutual funds and find out who performs better based on the Sharpe Index, Jensen Alpha, Escess Return of VAR (EROV) methods. ) and Sortino Ratio, and which sharia shama mutual funds performed better among them during the period 2010 to 2019. This study concludes that on average, both Indonesian and Malaysian Islamic equity mutual funds perform no better than market returns. However, the results of this research analysis have not made it possible to conclude that Indonesian Islamic stock mutual funds outperform Malaysian Islamic stock mutual funds or vice versa. This is because (1) both of them underperformed the market benchmark, (2) the results of the t-test show that based on the two measurement methods (Sharpe Index and EROV) there are significant differences, but based on the other two methods (Jensen Alpha and Sortino ratio) the t-test results -Test is not convincing enough to say that the average value of Jensen Alpha and IMF Sortino Ratio in Malaysia and Indonesia is significantly different. And (3) statistically, the samples of Indonesian and Malaysian Islamic stock mutual funds are not balanced.